2018
DOI: 10.1016/j.tranon.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenomics Analysis Reveals that TP53 Mutations Inhibit Tumor Immunity in Gastric Cancer

Abstract: Although immunotherapy continues to demonstrate efficacy in a variety of refractory cancers, currently, no any immunotherapeutic strategy is clinically used for gastric cancer (GC) except its microsatellite instable subtype. Thus, it is important to identify molecular biomarkers for predicting the responders to GC immunotherapy. TP53 mutations frequently occur in GC and are associated with unfavorable clinical outcomes in GC. We performed a comprehensive characterization of the associations between TP53 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
72
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 52 publications
18
72
5
Order By: Relevance
“…3 B). The result showed that TP53 had the highest mutation rate in GC, and has a significantly higher mutation rate in IM-L than in IM-H (Fisher's exact test, P = 0.04 (TCGA), P = 0.12 (ACRG)), which was consistent with our previous studies that TP53 mutations inhibit tumor immunity in GC [ 30 ]. MUC16 had the second highest mutation rate in GC and was also significantly higher in IM-L than in IM-H (Fisher's exact test, P = 0.002 (TCGA), P = 0.04 (ACRG)).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…3 B). The result showed that TP53 had the highest mutation rate in GC, and has a significantly higher mutation rate in IM-L than in IM-H (Fisher's exact test, P = 0.04 (TCGA), P = 0.12 (ACRG)), which was consistent with our previous studies that TP53 mutations inhibit tumor immunity in GC [ 30 ]. MUC16 had the second highest mutation rate in GC and was also significantly higher in IM-L than in IM-H (Fisher's exact test, P = 0.002 (TCGA), P = 0.04 (ACRG)).…”
Section: Resultssupporting
confidence: 90%
“…3 A). This is in accordance with our previous study showing that various immune signatures positively correlated with the MAPK, focal adhesion and Calcium signaling pathways in GC [ 30 ]. In contrast, the IM-L GC subtype was impoverished in immune signatures but enriched in base excision repair, DNA replication, homologous recombination, non-homologous end-joining and nucleotide excision repair ( Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The mutations of TP53 were mostly observed in non-immune class, and the proportion was only 5.4% in the immune activated subtype. Jiang et al [78] demonstrated that the TP53 mutation results in the depressed immune activity in gastric cancer, and the less active immune pathways and cell types are observed in TP53-mutated gastric cancer patients. Carlisle et al [79] also reported TP53 mutation correlates with the poor efficacy of immunotherapy after adjusting PD-L1 expression in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…( 20 ) It has previously been reported that there is a correlation between mtp53 and absence/reduced presence of immune cells in head and neck, and gastric cancers. ( 2325 ) However, it is not known whether this is the functional outcome of wildtype p53 loss or a gain-of-function activity of mtp53. Since mtp53 is associated with genomic instability, we speculated that it may alter signaling through the cGAS/STING/TBK1/IRF3 pathway to permit the accumulation of cytoplasmic DNA without triggering IRF3 activation.…”
Section: Introductionmentioning
confidence: 99%